2006
DOI: 10.1177/147470490600400115
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Simulation of Parental Investment Decisions: The Role of Future Reproductive Opportunities and Quality of Offspring in Determining Levels of Parental Investment

Abstract: Hagen's Defection Hypothesis (2002) predicts that a mother's age and the quality of her offspring are critical factors in determining her investment in her newborn. We tested this hypothesis using hamster races in which 113 college student participants received a hamster ("offspring") and 10 poker chips ("resources") to "invest" into the hamster based on information about the quality of the hamster and about the possibility of future races. Subjects invested the most in low quality offspring when they expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…However, it seems that some variables have more influence than others. For example, age was a discriminating variable, corroborating the prediction made by Parental Investment theory and authors (Keller & Chasiotis, 2007;Kramer & Lancaster, 2010;Turner, 2006). We observed that as reproductive potential decreases, maternal investment increases, since mothers in P2 and P3 profiles invested more than younger mothers in P1, and PROFILES OF MATERNAL CARE less than older mothers in P4, at least in one of the measures (stimulation scores).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, it seems that some variables have more influence than others. For example, age was a discriminating variable, corroborating the prediction made by Parental Investment theory and authors (Keller & Chasiotis, 2007;Kramer & Lancaster, 2010;Turner, 2006). We observed that as reproductive potential decreases, maternal investment increases, since mothers in P2 and P3 profiles invested more than younger mothers in P1, and PROFILES OF MATERNAL CARE less than older mothers in P4, at least in one of the measures (stimulation scores).…”
Section: Discussionsupporting
confidence: 89%
“…Mother's age is expected to affect fitness payoff of investment, as it is related to future reproductive prospects. As women get older future reproductive prospects decrease and, as a consequence, the value of current offspring (to mothers' fitness) rises, prompting the display of increased investment (Kramer & Lancaster, 2010;Turner, 2006). Ecological conditions, mainly represented by mothers' access to resources, are also expected to affect fitness payoff of investment.…”
mentioning
confidence: 99%
See 1 more Smart Citation